ENO1 contributes to 5-fluorouracil resistance in colorectal cancer cells via EMT pathway - Gu, Jinrong; Zhong, Kaiqiang; Wang, Longgang; Ni, Haishun; Zhao, Yirui; Wang, Xuchao; Yao, Yizhou; Jiang, Linhua; Wang, Bin; Zhu, Xinguo (Frontiers in Oncology, 2022)
Introduction Chemoresistance is a major barrier in the treatment of colorectal cancer (CRC) and many other cancers. ENO1 has been associated with various biological characteristics of CRC. This study aimed to investigate the function of ENO1 in regulating 5-Fluorouracil (5-FU) resistance in CRC. Methods ENO1 level in 120 pairs of tumor tissues and adjacent normal tissues was examined by immunohistochemistry, and the correlation between ENO1 expression and prognosis was explored by survival analysis. Its role and potential mechanisms in regulating 5-FU resistance in CRC were studied by Western blotting, MTT assay, colony formation assay and transwell invasion assay. Murine xenograft assay was implied to verify the results in vivo. Results Our study indicated that ENO1 was elevated in CRC tissues and was associated with poor patient prognosis. High levels of ENO1 expression were detected as a significant influencing factor for overall survival. Furthermore, ENO1 expression was found to have increased in drug-resistant cells (HCT116/5-FU and SW620/5-FU) constructed by increasing concentrations of 5-FU. Knockdown of ENO1 markedly increased the drug susceptibility and inhibited the proliferation and migration ability of HCT116/5-FU and SW620/5-FU cells. It was found that down-regulation of ENO1 inhibited the epithelial-mesenchymal transformation (EMT) signaling process. Finally, a murine xenograft assay verified that the depletion of ENO1 alleviated 5-FU resistance. Conclusion This study identified that ENO1 regulated 5-FU resistance via the EMT pathway and may be a novel target in the prevention and treatment of 5-FUresistant CRC.